2018
DOI: 10.2147/copd.s155985
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conjugated linoleic acid on oxidative stress and matrix metalloproteinases 2 and 9 in patients with COPD

Abstract: BackgroundNatural antioxidants in foods may be used in prevention and treatment of oxidative stress and inflammation in COPD. Therefore, this study aimed to evaluate the effect of conjugated linoleic acid (CLA) supplement as natural antioxidants on oxidative stress levels, and MMP2 and MMP9 serum levels in COPD patients.Materials and methodsThis clinical trial study was conducted on 90 (supplement group=45 and control group=45) COPD patients in Ardabil city, Iran, in 2015. After obtaining written consent, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…Oleic acid levels were significantly higher in Ricotta from the L‐group than in Ricotta from the P‐group ( P < 0.005), and the content was lowest in Ricotta from the group of sheep fed a typical milking ration. This result is valuable because CLA is recognised as beneficial for human health, by combating oxidative stress (Matin et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Oleic acid levels were significantly higher in Ricotta from the L‐group than in Ricotta from the P‐group ( P < 0.005), and the content was lowest in Ricotta from the group of sheep fed a typical milking ration. This result is valuable because CLA is recognised as beneficial for human health, by combating oxidative stress (Matin et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, it was desirable to assess the COPD patients’ nourishment. In fact, dietary aberrations could influence the OS/AOS biomarkers (Lu et al, 2018; Matin, Nemati, Ghobadi, Alipanah-Moghadam, & Rezagholizadeh, 2018). For example, it was demonstrated that oligomeric proanthocyanidins supplementation was effective in increasing the AOS capacity in patients with COPD (Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress causes overproduction of oxygen free radicals and disturbance in better function of the antioxidant system (21). CCl 4 and oxygen free-radical production is associated with inadequate enzymatic and non-enzymatic antioxidant status (22,23).…”
Section: The Effect Of Fme and CCL 4 On The Histology Of Testismentioning
confidence: 99%